If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1h = -9 + 2h Solving -1h = -9 + 2h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-2h' to each side of the equation. -1h + -2h = -9 + 2h + -2h Combine like terms: -1h + -2h = -3h -3h = -9 + 2h + -2h Combine like terms: 2h + -2h = 0 -3h = -9 + 0 -3h = -9 Divide each side by '-3'. h = 3 Simplifying h = 3
| 9v=40+v | | 2(5c+1)-33=3c+4 | | 37x+360y=1 | | 9(2x+1)=4x-8x | | -4f=-7f+6 | | -0.5t-(-0.5)=70 | | 3m+2m+m=18 | | 25/a=5 | | 12u-9u=15 | | 3-2x=9+x | | m-18/-1=-1 | | 6+10=-4(2x-4) | | 8+9n=10n | | w/8-2.1=14.9 | | u^2+6u-3=0 | | 13j+-11j=16 | | 1000=1000-100i | | -10w+7w=9 | | 5x+4(2x+10)=13x+40 | | 5.5a+15=81 | | 8d+9=7d | | 1000=1000-100x | | 5(x+4)+2=10x+5(x+2) | | 4d-d=6 | | 11x-250=3x | | -9n+11=-8n | | -34-4y=5(9y-8) | | 4ncubed-9n=0 | | 7y-2x+14=0 | | -2x+10+7x=16x+7 | | 3(4x-80)+6x=2(x+40) | | U/4-1=3 |